Survival analysis of COVID-19 versus non-COVID-19 patients requiring intensive care for acute respiratory distress syndrome: An observational retrospective study - Paulo Navas Boada; Kevin Chamorro; Santiago Ballaz (Canadian Journal of Respiratory Therapy)
# Background/Aim